Cortistatin, a novel cardiovascular protective peptide - Liang, Juan (Cardiovasc Diagn Ther, 2019)
Cortistatin (CST) is a small molecule bioactive peptide containing an FWKT tetramer. It is widely distributed in nervous, immune and endocrine systems. Many studies have shown that CST can exert many biological effects, for example: regulating sleep, learning and memory processes, inducing immune tolerance, inhibiting inflammatory responses, and regulating endocrine metabolism. Notably, it is found that CST and its receptors are also widely distributed in the cardiovascular system, such as the aorta, coronary arteries and heart. In recent years, increasing studies have shown that CST played an important role in the development of cardiovascular diseases, such as reducing myocardial damage, inhibiting autoimmune myocarditis, alleviating vascular smooth muscle cell (VSMC) proliferation and migration, reducing vascular calcification (VC), and inhibiting atherosclerosis and aneurysm formation. Therefore, we reviewed the cardiovascular effects of CST in the heart and blood vessels, which will help to understand the role of CST and its receptors in the pathogenesis of cardiovascular diseases, and highlight novel strategies and targets for the prevention and treatment of cardiovascular diseases.